Analisis Semiotika Komik Digital The Secret Of Angel terhadap Kepercayaan Diri Perempuan - Nur Azizah; Rizky Fauzi (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
Digital comics are comics that are published visually through websites or applications. Webtoon is one of the popular applications used to read digital comics. Webtoon provides a lot of comics, one of which is The Secret of Angel. This study aims to find out how the Semiotic Analysis of Digital Comics The Secret Of Angel, besides that this study aims to find out the influence of Digital Comics The Secret Of Angel on women's self-confidence. The method used in this research is descriptive qualitative which aims to solve problems, summarize various situations or events by presenting data, analyzing data, and explaining data. The results of the study prove that the digital comic